Molecular Basis Underlying Leaf Variegation of a Moth Orchid Mutant (Phalaenopsis aphrodite subsp. formosana) - Tsai, Chi-Chu; Wu, Yu-Jen; Sheue, Chiou-Rong; Liao, Pei-Chun; Chen, Ying-Hao; Li, Shu-Ju; Liu, Jian-Wei; Chang, Han-Tsung; Liu, Wen-Lin; Ko, Ya-Zhu; Chiang, Yu-Chung (Frontiers in Plant Science, 2017)
Leaf variegation is often the focus of plant breeding. Here we studied a variegated mutant of Phalaenopsis aphrodite subsp. formosana, which is usually used as a parent of horticultural breeding, to understand its anatomic and genetic regulatory mechanisms in variegation. Chloroplasts with well-organized thylakoids and starch grains were found only in the mesophyll cells of green sectors but not of yellow sectors, confirming that the variegation belongs to the chlorophyll type. The two-dimensional electrophoresis and LC/MS/MS also reveal differential expressions of PsbP and PsbO between the green and yellow leaf sectors. Full-length cDNA sequencing revealed that mutant transcripts were caused by intron retention. When conditioning on the total RNA expression, we found that the functional transcript of PsbO and mutant transcript of PsbP are higher expressed in the yellow sector than in the green sector, suggesting that the post-transcriptional regulation of PsbO and PsbP differentiates the performance between green and yellow sectors. Because PsbP plays an important role in the stability of thylakoid folding, we suggest that the negative regulation of PsbP may inhibit thylakoid development in the yellow sectors. This causes chlorophyll deficiency in the yellow sectors and results in leaf variegation. We also provide evidence of the link of virus CymMV and the formation of variegation according to the differential expression of CymMV between green and yellow sectors.